(untitled) (Research, Society and Development, 2025)
Introduction: Gastric and duodenal ulcers are prevalent conditions that affect the mucosa of the stomach and duodenum, respectively, and are associated with a significant impact on public health. Therefore, this article aims to provide a quantitative and temporal analysis of the epidemiological characteristics of gastric and duodenal ulcers from January 2017 to September 2024. Methodology: This is an epidemiological study carried out based on data from the health information department of the SUS (Unified Health System). The variables used were: hospital admissions, deaths, age group, color/race, sex, hospital expenses, and health macroregion.Methodology: This is an epidemiological study carried out based on data from the health information department of the SUS (Unified Health System). The variables used were: hospital admissions, deaths, age group, color/race, sex, hospital expenses and health macro-region. Results: 86,505 hospitalizations were due to ulcers and in the period analyzed the highest number of hospitalizations was in 2013. The Southeast region was the most reported regarding the number of hospitalizations and the one where most individuals died due to complications. The largest age group affected was between 60 and 69 years old. Males were the gender most affected by this pathology. Regarding ethnicity, more brown patients were hospitalized. In addition, the Southeast region had the highest average number of days of hospitalization. Conclusion: Understanding these trends is essential for formulating effective public health policies and for better allocation of resources for treating these diseases. In addition, epidemiological analysis can guide preventive actions, such as educational campaigns on the appropriate use of NSAIDs and the need to eradicate H. pylori.